Effects of rumen-protected fat on changes of metabolites and reproductive genes in testes of Malin rams - Ismail, Alifah (2022)
An energy-based diet is necessary for male animals especially during breeding activities to improve most of the reproduction parameters. In addition to grains, the consumption of fat can also contribute to the activity. A previous study reported that RPF did improve reproductive performance by increasing sperm quality in Malin ram. The present research was conducted to understand the RPF influence on the blood biochemistry profiles, metabolites changes and genes associated to the male reproduction organ at the molecular level that can reduce the knowledge gap in this area. Twenty Malin rams with average bodyweight of 36.6kg  5.57 kg, aged 10 to 14 months reared at The National Institute Animal Biodiversity Jerantut, Pahang were assigned randomly into four experimental groups. Each treatment group was fed with different lipid types that composed with different fatty acids property: A; basal diet without rumen-protected fat (RPF), B; basal diet with 2% prilled fat, C; basal diet with 2 % calcium salt and D; basal diet with 2% canola oil for comparison. The period of the experiment was 12 weeks the animals were allowed for 2 weeks of adaptation period and 10 weeks of feeding trials. Blood was taken via jugular vein at every fortnight and four out of five animals from each group were slaughtered at the end of the experiment. The testes were excised from the slaughtered animals for metabolites studies using LC-MS analysis and gene expression analysis using quantitative Real-Time PCR (q-PCR). In this study, the blood biochemistry test was also done to determine the effects of RPF on glucose, cholesterol, triglycerides and low-density lipoprotein (LDL), high-density lipoprotein (HDL) level. The genes tested in the present study were associated to testes development and spermatogenesis (reproductive genes in testes: ODF1, SERPINA10, CatSper4 AdipoR2 and DAZL). The blood biochemistry result showed the cholesterol, triglycerides, HDL and LDL did not differ in all groups. Feeding RPF with calcium salt (Treatment C) has resulted in the up-regulation effects, which are more than two folds in all reproductive genes that have been studied in the testes. The present study showed there were metabolites changes occurred between the groups and identified 44 important putative metabolites present in the testes via preliminary screening of LC-MS. The identified putative metabolites in the treatment groups demonstrate the findings of 10-hydroxy-(2E,8E)-decadien-4-ynoic acid in the control group, 1-Heneicosanoyl-2- docosanoyl-3-sn glycerol in the prilled fat group and the same putative metabolites which are Adenosine 5’ pentaphosphate and PE(24:0/24:1(15Z) in calcium salt and canola oil group. In conclusion, feeding of RPF to the animals as a source of energy has no impact on the blood lipid profiles which could be due to the metabolic processes efficiency since there were metabolites changes that occurred according to the type of fat given. The metabolism efficiency of the RPF especially with calcium salt to produce fatty acids as a source of energy indirectly expressed the genes related to reproduction performances in the testes.